2010
DOI: 10.1177/1362168810383329
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simultaneous use of careful online planning and task repetition on accuracy, complexity, and fluency in EFL learners’ oral production

Abstract: This article reports on a study that was primarily aimed at investigating the effects of simultaneous use of careful online planning and task repetition on accuracy, complexity, and fluency in the oral production of learners of English as a foreign language (EFL). The effects of four planning and task repetition conditions (i.e. careful online planning without task repetition, pressured online planning with task repetition, careful online planning with task repetition, and pressured online planning without tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(67 citation statements)
references
References 22 publications
9
52
1
4
Order By: Relevance
“…A study conducted by Ahmadian and Tavakoli (2011) in an EFL class in Iran, investigated the effects of simultaneous use of careful online planning and task repetition on accuracy, complexity, and fluency in the oral production of EFL learners. The results obtained from one-way ANOVAs revealed that the opportunity to engage simultaneously in careful online planning and task repetition enhances accuracy, complexity, and fluency significantly.…”
Section: Pre-task Planning Studiesmentioning
confidence: 99%
“…A study conducted by Ahmadian and Tavakoli (2011) in an EFL class in Iran, investigated the effects of simultaneous use of careful online planning and task repetition on accuracy, complexity, and fluency in the oral production of EFL learners. The results obtained from one-way ANOVAs revealed that the opportunity to engage simultaneously in careful online planning and task repetition enhances accuracy, complexity, and fluency significantly.…”
Section: Pre-task Planning Studiesmentioning
confidence: 99%
“…Additionally, the issue of modality, which is considered an indispensable component of task performance, has garnered little attention in task-based planning studies. A plethora of literature exists investigating the effects of planning time conditions on the CAF triad in speaking tasks and supporting their effects on different dimensions of language performance (Ortega, 1999;Skehan and Foster, 1999;Yuan and Ellis, 2003;Ahmadian and Tavakoli, 2011). However, a paucity of literature exists regarding the influences of planning time conditions on complexity, accuracy and fluency in writing tasks, particularly in an EFL context.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, "to enhance both the validity of the assessments and the comparability of the results" (Ahmadian and Tavakoli, 2011) …”
Section: Grammatical Accuracymentioning
confidence: 99%